1175. Pulmonary Aspergillosis in Critically Ill Patients with COVID-19: A Case Series. (31st December 2020) - Mitaka, Hayato; Perlman, David C; Javaid, Waleed; Salomon, Nadim
Abstract: Background: Invasive pulmonary aspergillosis (IPA) has been reported in critically ill patients without pre-existing immunocompromising conditions. However, there are scant data on pulmonary aspergillosis in patients with COVID-19. Methods: We performed a retrospective review of pharmacy records of antifungal use during 3/21-4/22, 2020, and collect longitudinal clinical data. Cases were then classified by the clinical algorithm for IPA in the ICU (AspICU). Results: 7 out of 18 (39%) patients who received antifungal therapy had Aspergillus fumigatus in tracheal aspirate specimens while mechanically ventilated in the ICU. None of the patients had EORTC/MSG host factors. Median time from admission to the date of positive respiratory culture was 9 days (range: 2-15). High-dose glucocorticoids were started a mean of 5.6 days (range 3-8) before the positive respiratory culture in 5 and on the day of the culture in 2. Six received 583-1000 mg equivalent of prednisone. Two received Tocilizumab. By AspICU criteria, 4 had putative IPA. Radiographic abnormalities included cavitary pneumonia, opacities with dense consolidation, worsening infiltrates, and diffuse interstitial and patchy hazy opacities. Compatible signs included worsening respiratory failure in 3 and fever after 3 days of antibacterial agents in 1. Associated findings were leukocytosis in 4, > 1 positive cultures in 3, high procalcitonin in 2, and positive serum galactomannan in 1. The remaining three were classified as colonization as they lacked compatible signs. One had concomitant Klebsiella aerogenes pneumonia with bacteremia, and two later developed Candidemia and Stenotrophomonas maltophilia pneumonia, respectively. All 3 had fever with leukocytosis. One had elevated procalcitonin. Six received antifungal therapy; one did not due to goals of care. All 7 patients expired despite ICU care. Conclusion: The critically ill patients with severe COVID-19 in whom respiratory culture grew Aspergillus fumigatus showed very high mortality despite antifungal treatment. By AspICU algorithm, 4 patients had putative IPA. Further data on risk factors and clinical predictors of IPA in COVID-19 are needed. Disclosures: All Authors : No reported disclosures